Multifunctional Carbon Aerogels with Hierarchical Anisotropic Structure Derived from Lignin and Cellulose Nanofibers for CO(2) Capture and Energy Storage - Geng, Shiyu (ACS Appl Mater Interfaces, 2020)
[Image: see text] In current times, CO(2) capture and lightweight energy storage are receiving significant attention and will be vital functions in next-generation materials. Porous carbonaceous materials have great potential in these areas, whereas most of the developed carbon materials still have significant limitations, such as nonrenewable resources, complex and costly processing, or the absence of tailorable structure. In this study, a new strategy is developed for using the currently underutilized lignin and cellulose nanofibers, which can be extracted from renewable resources to produce high-performance multifunctional carbon aerogels with a tailorable, anisotropic pore structure. Both the macro- and microstructure of the carbon aerogels can be simultaneously controlled by carefully tuning the weight ratio of lignin to cellulose nanofibers in the precursors, which considerably influences their final porosity and surface area. The designed carbon aerogels demonstrate excellent performance in both CO(2) capture and capacitive energy storage, and the best results exhibit a CO(2) adsorption capacity of 5.23 mmol g(–1) at 273 K and 100 kPa and a specific electrical double-layer capacitance of 124 F g(–1) at a current density of 0.2 A g(–1), indicating that they have great future potential in the relevant applications.